2023
DOI: 10.1007/s40265-022-01828-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Chemotherapy for Unresectable Peritoneal Surface Malignancies

Abstract: Malignancies of the peritoneal cavity are associated with a dismal prognosis. Systemic chemotherapy is the gold standard for patients with unresectable peritoneal disease, but its intraperitoneal effect is hampered by the peritoneal-plasma barrier. Intraperitoneal chemotherapy, which is administered repeatedly into the peritoneal cavity through a peritoneal implanted port, could provide a novel treatment modality for this patient population. This review provides a systematic overview of intraperitoneal used dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 136 publications
0
26
0
Order By: Relevance
“…(3) The presence of the peritoneal−plasma barrier also prolongs the exposure time of cancer cells to chemotherapeutic drugs and reduces the systemic toxicity of chemotherapeutic drugs. 6,61,67 It is these advantages that have led to promising results for intraperitoneal chemotherapy in many clinical trials for the treatment of peritoneal metastatic cancer; for example, in a preliminary study in 2004, Mahteme et al showed that the addition of intraperitoneal chemotherapy to the treatment of peritoneal metastatic cancer resulted in a survival benefit for patients. 68 The selection of chemotherapeutic drugs is particularly important when intraperitoneal chemotherapy is used in clinical practice, which is also an important factor to ensure the good therapeutic effect of intraperitoneal chemotherapy in the treatment of peritoneal metastatic cancer.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The presence of the peritoneal−plasma barrier also prolongs the exposure time of cancer cells to chemotherapeutic drugs and reduces the systemic toxicity of chemotherapeutic drugs. 6,61,67 It is these advantages that have led to promising results for intraperitoneal chemotherapy in many clinical trials for the treatment of peritoneal metastatic cancer; for example, in a preliminary study in 2004, Mahteme et al showed that the addition of intraperitoneal chemotherapy to the treatment of peritoneal metastatic cancer resulted in a survival benefit for patients. 68 The selection of chemotherapeutic drugs is particularly important when intraperitoneal chemotherapy is used in clinical practice, which is also an important factor to ensure the good therapeutic effect of intraperitoneal chemotherapy in the treatment of peritoneal metastatic cancer.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%
“…(2) Intraperitoneal chemotherapy allows for higher intraperitoneal drug concentrations compared to intravenous administration, probably due to the peritoneal–plasma barrier, which limits the reabsorption of intraperitoneal chemotherapeutic drugs into the body circulation. (3) The presence of the peritoneal–plasma barrier also prolongs the exposure time of cancer cells to chemotherapeutic drugs and reduces the systemic toxicity of chemotherapeutic drugs. ,, It is these advantages that have led to promising results for intraperitoneal chemotherapy in many clinical trials for the treatment of peritoneal metastatic cancer; for example, in a preliminary study in 2004, Mahteme et al showed that the addition of intraperitoneal chemotherapy to the treatment of peritoneal metastatic cancer resulted in a survival benefit for patients …”
Section: Clinical Treatment Options For Peritoneal Metastatic Cancermentioning
confidence: 99%
“…Chemotherapy resistance is a common challenge in tumor therapy because tumor cells acquire resistance to chemotherapeutic drugs and are unable to effectively kill tumor cells 16,17 . This phenomenon is usually caused by biochemical mechanisms within the tumor cells, such as drug efflux, drug catabolism, DNA repair 18–23 .…”
Section: Introductionmentioning
confidence: 99%
“…In patients with more extensive peritoneal metastases, repeated administration of cytotoxic drugs into the peritoneal cavity has been investigated. Normothermic catheter-based intraperitoneal chemotherapy and normothermic pressurized intraperitoneal aerosol chemotherapy (PIPAC) are methods to deliver intraperitoneal chemotherapy with a palliative intent 9 . In this way, higher intraperitoneal concentrations of cytotoxic drugs can be achieved compared to intravenous administration 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Normothermic catheter-based intraperitoneal chemotherapy and normothermic pressurized intraperitoneal aerosol chemotherapy (PIPAC) are methods to deliver intraperitoneal chemotherapy with a palliative intent 9 . In this way, higher intraperitoneal concentrations of cytotoxic drugs can be achieved compared to intravenous administration 9 . For normothermic catheter-based intraperitoneal chemotherapy, an access port is placed subcutaneously and connected to an intraperitoneal catheter.…”
Section: Introductionmentioning
confidence: 99%